The Wounds of Our Mother Psychoanalysis New Models for Psychoanalysis in Crisis - Azzone, Paolo (IntechOpen, 2023)
Psychoanalysis is facing a severe crisis. Contemporary epistemology relies on an extreme materialistic reductionism and human sciences seem eager to conform as much as possible to the models and procedures of hardcore science and somatic medicine. Western society is currently harboring a deep mistrust for a discipline that fully incorporates the flesh and blood of interpersonal emotions. The standing of psychoanalysis as a basic dimension of human culture is threatened more than ever and psychoanalysis is badly in need of new strategies and new models. Unluckily, and - I must add - quite dismayingly, psychoanalytic institutions have generally appeared shy, even helpless in front of such an impressive army of critics and opponents. Nowadays, psychoanalysis appears weak. We may even qualify it as wounded. The development of the interpersonal model and of the Kleinian school in the second half of the last century has set the stage for the emergence of an original conceptualization of the unconscious mind. Within the intersubjective paradigm, the psychoanalytic situation is conceptualized as an interpersonal field to which both the analyst and the patient substantially contribute. We believe that the failure to fully integrate such an intersubjective dimension in both psychoanalytic theory and practice amounts to a core liability in 21st-century psychoanalysis. This book gathers several contributions discussing the contemporary crises of psychoanalysis and offering new perspectives. Some contributors lament that the prevailing psychoanalytic theory and clinical practice have been unable to stay true to the fundamentals of the discipline. Other chapters explore the intersections between psychoanalysis and neural sciences. Finally, the last section demonstrates how psychoanalysis can still be fruitfully applied to the understanding of contemporary culture and society, including basic issues such as identity politics and climate change.